Student Soft Skills in Learning Support Services with Webinar Tutorials (Tuweb) and Online Tutorials (Tuton) : A Study in Indonesia Open University’s Postgraduate Program - Nirmala, Sri Dewi; Afriani, Afriani; Isfarudi, Isfarudi; Ramdhani, Sendi; Pannen, Paulina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze students’ soft skills in learning support services, namely webinar tutorial (tuweb) and online tutorial (tuton), and the relationship of the soft skills to the student’s grades in both tuton and tuweb, Indonesia Open University’s Postgraduate Program. Aspects of the soft skills developed were 1) teamwork; 2) communication through Tuweb’s discussion forums; 3) oral communication; and 4) leadership. This study used a survey method with quantitative approach. The participants were 99 students from two courses. The research instrument was online survey questionnaire using Microsoft Forms. Data analysis used descriptive statistics, correlation, and regression analysis. The results of the study were 1) students’ soft skills on tuton and tuweb have developed as expected; 2) teamwork and communication skills correlate with students’ attendance and discussion; 3) oral communication and leadership skills do not correlate students’ discussions and assignments; and 4) teamwork and written communication skills had the most significant contribution to the tutorials’ grade compared to oral communication and leadership skills.